Common-Ground Bridgeless Unity Power Factor Single-Phase Rectifier - Ivo Barbi; Hugo Rolando Estofanero Larico (IEEE Access)
A common AC and DC ground bridgeless power converter topology is presented that performs the near-unity power factor function with low harmonic distortion of a single-phase rectifier with sinusoidal input line voltage. The operation principle and design-oriented analysis are presented, along with the transfer functions and closed-loop input current control strategy. A non-optimized experimental prototype was developed and tested in the laboratory to validate the operating principle and the results of theoretical analysis. The distinctive feature of the proposed rectifier is that it eliminates the leakage current that circulates through the parasitic capacitances existing between the power semiconductor and heatsink, which causes common-mode electromagnetic interference in conventional boost-based PFC rectifiers.